Reinventing Representations of “Local” Identity and Culture - Seraina Hürlemann (Via@)
This article explores social processes contributing to the reinvention of tourist destinations using ethnographic data collected at the case study site in Lashi Hai, a rural area in north-west Yunnan, China. Rather than reducing the reinvention process to marketing strategies or official development plans, the article shows that it may in fact reflect deeper social tendencies and is not only limited to the changing demands of visitors. Representing “local” identity, the reinvention of touristic places also becomes subject to negotiation among resident populations, contesting the values and symbolic statements applied to represent their “own” culture. It will be demonstrated that there are various important players involved in this process of reinvention, ranging from a strong central government, official development agencies and private investors to local cooperatives and finally individual residents – all with a stake in shaping and creating what is perceived as the “local” identity and culture.